Digital Formats for Community Participation in Health Promotion and Prevention Activities: A Scoping Review - Schroeer, Claudia; Voss, Stephan; Jung-Sievers, Caroline; Coenen, Michaela (Frontiers in Public Health, 2021)
Objectives: Digital technologies in public health are primarily used in medical settings and mostly on an individual and passive way of use. There are research gaps on digital media facilitating participation, empowerment, community engagement, and participatory research in community settings. This scoping review aims to map existing literature on digital formats that enable participation in the field of health promotion and prevention in community settings. Design: The databases Medline, EMBASE, and PsycINFO were used to identify studies published from 2010 up to date (date of literature search) onward that used digital formats in all or in the main sequences of the process to enable high levels of participation in health promotion and prevention activities in community settings. Results: This review identified nine out of 11 included studies relevant to the research question. We found five studies that applied qualitative participatory research, two studies on peer support and one study each on empowerment and crowdsourcing. The digital technologies used varied widely and included social media platforms, bulletin boards, online forum webpages, and customized web providers and programs. Most studies mentioned anonymity, flexibility, and convenience as benefits of digital interventions. Some papers reported limitations such as difficulties by interpreting written-only data or the possibility of selection bias due to the digital divide. Conclusion: This scoping review identified only few studies relevant to our objective, indicating an existing gap in research on this topic. Digital formats were found to be particularly suitable for purposes where anonymity and flexibility are beneficial, such as for online peer exchange and peer support programs.